Praimago Density of Aedes Sp and Its Relationship with the Incidence of DHF in Kupang City - Wanti, Wanti; Sila, Oktofianus; Irfan, Irfan; Rahmawati, Ety; Sadukh, Johanes Pitreyadi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Mosquito density may represent the bionomic of Aedes sp and the risk of spreading the disease. The Indonesian Ministry of Health has been using ABJ, HI, CI, BI and Pupa Index (PI) to calculate the density of Aedes sp praimago and assess the risk of dengue transmission in an area, so it is necessary to look for an index that describes the individual risk of dengue transmission. The research objective was to analyze the relationship between praimago density of Aedes sp on the incidence of dengue fever in Kupang City, where in Kupang City. The research was conducted in 25 urban villages. Samples were taken from 20 people per sub-district obtained by cluster sampling, namely the center point is the DHF sufferer, then the nearest house was searched within a radius of 100 meters until a total of 20 houses were reached or 500 houses for Kupang City. The independent variables were larvae / pupa density (HP, PC, CPP, LH, PH, LCIH, PCIH, LPCIH, PPCIH, LPH, PPH) and egg density (TE, EDH, OIH), while the dependent variable was the incidence of DHF. Praimago density was determined by conducting an entomological survey in the form of a survey of eggs and larvae of Aedes sp. The data were processed to see the density of larvae and eggs per house, then statistically analyzed using independent t test, Chi Square, and Pearson Correlation. The study found that there was a relationship between larvae / pupa density (HP, PC, CPP, LH, LCIH, LPCIH, LPH) and egg density (TE, EDH, OIH) with the incidence of DHF. It concluded that the density of egg density and larvae / pupa density in a house can be used to estimate the risk of dengue fever from family members in the house.